(untitled) (Journal of Academic Finance, 2023)
Purpose: This study was carried out to understand the relationship between credit management and the financial performance of Micro Finance Institutions, taking a sample of 43 MFIs administrators in the towns of Dschang, Mbouda and Bafoussam of Cameron. Method: The study applied a quantitative research design, where questionnaires were used. Data was collected from both primary and secondary sources. Data was processed and analyzed using formal tables, pie charts, multiple linear regressions, and Anova, chi-squared, Cronbash’s Alpha, Pearson tests were carried out to understand the relationship between credit management and financial performance Microfinance Institution in Cameroon. A total of 43 respondents were considered out of the entire population. Findings: Findings indicate that credit policies, debt recovery technique mechanisms are significant and positively related to the portfolio quality of MFIs in Cameroon. More specifically, good lending policies such as proper study of the loan documents, group liability, monitoring repayment frequency would increase financial performance. In addition, recovery techniques such as constant customer reminder, prolonging recovery period, penalties etc, enabled MFIs to perform financially well. Originality value: This study explores and shed light on an important factor responsible in majority for the unpaid installment debts in the Cameroon context; the MFI itself through the personal and friendly relationships with clients. Thus we provide practical strategies for the recovery of these debts till the last franc. In addition, we show that these strategies increase MFI’s sustainability across their profitability.